2013
DOI: 10.1111/dsu.12177
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Patient Satisfaction of a Monophasic Cohesive Polydensified Matrix Versus a Biphasic Nonanimal Stabilized Hyaluronic Acid Filler After Single Injection in Nasolabial Folds

Abstract: A single intradermal injection of a monophasic CPMHA and a biphasic NASHA filler showed significant improvements in WSRS and measured wrinkle depth up to 48 weeks for both fillers and significant differences in injection comfort and patient satisfaction in favor of CPMHA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 23 publications
1
58
0
Order By: Relevance
“…The two interesting objective methods are the cutometer and the 3D imaging which are both non-invasive, reliable and easy to use tools. Measuring instruments, including the chromatometer, corneometer, tawameter, visiometer and sebumeter, are increasingly used, [9,10,11,16,19,20,26,33,36,38,41,43] allowing for quantitative results and an objective comparison between the baseline and the post-treatment period. These instruments are commonly used in dermatological and cosmetic studies and have been successfully applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The two interesting objective methods are the cutometer and the 3D imaging which are both non-invasive, reliable and easy to use tools. Measuring instruments, including the chromatometer, corneometer, tawameter, visiometer and sebumeter, are increasingly used, [9,10,11,16,19,20,26,33,36,38,41,43] allowing for quantitative results and an objective comparison between the baseline and the post-treatment period. These instruments are commonly used in dermatological and cosmetic studies and have been successfully applied.…”
Section: Discussionmentioning
confidence: 99%
“…For example in the study by Calabaro et al [9], the WSRS was combined with the use of a corneometer, tewameter and cutometer to assess facial wrinkle improvement after topical application of nifedipine. Overall, the WSRS is used to assess the efficacy of different hyaluronic acid formulations on nasolabial folds in combination with 3D imaging or reflectance confocal microscopy (RCM) [10,11]. Moreover, the GAIS is combined with a histological analysis to test the efficacy of mesotherapy on skin rejuvenation [12] and with midface volume scale score for the treatment of midface volume loss by large gel hyaluronic acid.…”
Section: Objective Methods To Assess Facial Rejuvenation Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of volume augmentation in the human body is generally persistent for 6-18 months depending on the injection site, type of HA formulation, and individual patient's metabolism [15,16]. According to several investigations, a monophasic, non-cross-linked HA with uniform particle size results in uniform spreading and defect augmentation compared to biphasic HA product [17]. On the other hand, Röck et al [18] reported excessive fibroblast proliferation induced by non-cross-linked HA formulation, and Wang et al [19] reported the de novo collagen production induced by cross-linked HA in photo-damaged human skin.…”
Section: Discussionmentioning
confidence: 99%